Clinical significance of the De Ritis ratio for detecting prostate cancer in a repeat prostate biopsy - Heon Ha (Investigative and Clinical Urology, 2019)
Purpose: We evaluated factors predicting a positive repeat biopsy result in patients with an initial negative prostate biopsy result. Materials and Methods: This study included 124 patients in whom prostate cancer (PCa) was not detected in the initial transrectal ultrasound-guided prostate biopsy and who underwent repeat biopsy from January 2011 to December 2017. Patients without PCa in both initial and repeat prostate biopsies were designated as group 1 (n=82), and those in whom PCa was detected on a repeat prostate biopsy were designated as group 2 (n=42). Among group 2 patients, 6 had insignificant PCa according to the Epstein criteria and were combined with group 1 patients to make up group A (n=88). Patients with significant PCa were categorized as group B (n=36). We compared clinicopathologic characteristics between the groups. Results: Multivariate analysis showed that age (p=0.018) and detection of atypical small acinar proliferation (ASAP) or ≥3 cores of high-grade prostatic intraepithelial neoplasia (HGPIN) (p=0.011) on the initial biopsy were predictive factors for a positive result on a repeat biopsy. When we compared group A and group B, age (p=0.004) and the De Ritis ratio (p=0.024) were significantly higher in group B in the multivariate analysis. Conclusions: Age and the detection of ASAP or ≥3 cores of HGPIN on the initial biopsy were associated with detection of PCa on a repeat biopsy. Age and the De Ritis ratio were found to be predictive factors for the detection of clinically significant PCa on a repeat biopsy.